Bolus Arrival Time and Cerebral Blood Flow Responses to Hypercarbia. Issue 7 (July 2014) - Donahue, Manus J; Faraco, Carlos C; Strother, Megan K; Chappell, Michael A; Rane, Swati; Dethrage, Lindsey M; Hendrikse, Jeroen; Siero, Jeroen CW
The purpose of this study was to evaluate how cerebral blood flow and bolus arrival time (BAT) measures derived from arterial spin labeling (ASL) MRI data change for different hypercarbic gas stimuli. Pseudocontinuous ASL (pCASL) was applied (3.0T; spatial resolution = 4 × 4 × 7 mm 3 ; repetition time/echo time ( TR/TE ) = 3, 600/11 ms) sequentially in healthy volunteers ( n = 12; age = 30±4 years) for separate experiments in which (i) normocarbic normoxia (i.e., room air), hypercarbic normoxia (i.e., 5% CO2 /21% O2 /74% N2 ), and hypercarbic hyperoxia (i.e., carbogen: 5% CO2 /95% O2 ) gas was administered (12 L/minute). Cerebral blood flow and BAT changes were quantified using models that account for macrovascular signal and partial volume effects in all gray matter and regionally in cerebellar, temporal, occipital, frontal, and parietal lobes. Regional reductions in BAT of 4.6% to 7.7% and 3.3% to 6.6% were found in response to hypercarbic normoxia and hypercarbic hyperoxia, respectively. Cerebral blood flow increased by 8.2% to 27.8% and 3.5% to 19.8% for hypercarbic normoxia and hypercarbic hyperoxia, respectively. These findings indicate that changes in BAT values may bias functional ASL data and thus should be considered when choosing appropriate experimental parameters in calibrated functional magnetic resonance imaging or ASL cerebrovascular reactivity experiments that use hypercarbic gas stimuli.